The Impact of Cultural Diversity on Small Business Strategy - Alexandra Galli-Debicella (Journal of Management Research, 2024)
Academic literature is rich with studies of small firms and of cultural diversity in the workforce—but very few academic studies have researched the intersection of the two. Academic research has looked at small firms and the factors that impact small firm performance, growth, and failure. Cultural diversity studies have included research focused directly on the degree of cultural diversity of firms regardless of size. However, the impact of cultural diversity on small firm strategy has not been extensively reviewed. The intersection of small firms and cultural diversity yields a number of interesting hypotheses. Specifically, this paper examines: (1) The level of managerial skill at diversity management has a disproportionately large impact on small business capability to develop competitive advantage out of diversity; (2) Niche-based cultural competitive advantage is stronger in small business than in large organizations; and (3) There is an inverse correlation between number of cultures and strength of diversity strategy in small firms—while the correlation is positive in larger firms that can handle more complex interactions.